2012
DOI: 10.1186/1754-6834-5-46
|View full text |Cite
|
Sign up to set email alerts
|

Improved ethanol production by a xylose-fermenting recombinant yeast strain constructed through a modified genome shuffling method

Abstract: BackgroundXylose is the second most abundant carbohydrate in the lignocellulosic biomass hydrolysate. The fermentation of xylose is essential for the bioconversion of lignocelluloses to fuels and chemicals. However the wild-type strains of Saccharomyces cerevisiae are unable to utilize xylose. Many efforts have been made to construct recombinant yeast strains to enhance xylose fermentation over the past few decades. Xylose fermentation remains challenging due to the complexity of lignocellulosic biomass hydrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 17 publications
(27 reference statements)
0
56
0
2
Order By: Relevance
“…Recently, several research groups have investigated the termite digestome, hypothesizing that auxiliary redox mechanisms may be involved in lignocellulose degradation [5, 26, 27, 3234]. Among these studies, Scharf and Sethi [27] reported that an AKR acted synergically with termite and symbiotic GHs during pine wood hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several research groups have investigated the termite digestome, hypothesizing that auxiliary redox mechanisms may be involved in lignocellulose degradation [5, 26, 27, 3234]. Among these studies, Scharf and Sethi [27] reported that an AKR acted synergically with termite and symbiotic GHs during pine wood hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…The detoxification of hemicellulosic hydrolysates is of biotechnological interest, and many detoxification methods have been reported in the literature [9, 11, 14, 17, 32, 51]. Laccases and peroxidases are being applied in the development of enzymatic cocktails for detoxification of lignin components, consuming or generating ROS such as H 2 O 2 to remove soluble lignin in fermentation medium; thus, PAD enzymes such as Cg AKR-1 could also be applied for this purpose [10, 52, 53].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, as a valuable synthetic building block, xylitol is one of the top 12 value-added materials produced from biomass, and thereby serves as a key economic driver of the biorefinery concept [7]. The major traits required of an industrial strain for fermenting lignocellulosic hydrolysate are efficient utilization of hexoses and pentoses, fast fermentation rates, high product yield and high tolerance of sugars, and fermentation inhibitors [3,8].…”
Section: Introductionmentioning
confidence: 99%
“…Xylose is the second most abundant sugar present in lignocellulosic biomass, after glucose [3]. Efficient fermentation of xylose is necessary to develop economically viable processes using lignocellulosic biomass [4].…”
Section: Introductionmentioning
confidence: 99%
“…To improve the ability of K. marxianus to ferment xylose into ethanol, K. marxianus G2-16-1 was subjected to electroporation-mediated genome shuffling (Zhang and Geng 2012) using the chromosomal DNA of Pichia stipitis JCM 10742 T , a high-xylose fermenting yeast (Du Preez and Prior 1985) as the chromosomal donor. This study is the first report of genome shuffling between K. marxianus and P. stipitis.…”
Section: Introductionmentioning
confidence: 99%